The Analysis Study of Low Dose Aspirin for Prevention of Superimposed Preeclampsia in Women with Chronic Hypertension: A Comprehensive Systematic Review - BrGirsang, Lora Coarnita; Anisa, Anisa (International Medical Journal Corp. Ltd, 2024)
Background: Chronic hypertension (cHTN) is the greatest risk factor for the development of preeclampsia. Low-dose aspirin has been used as a therapy for preeclampsia prevention. This study aims to show effectiveness of low dose aspirin for prevention of superimposed preeclampsia in women with chronic hypertension. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. Results: We compiled a total of 16 papers, 9 of which came from PubMed and 7 of which came from ScienceDirect. We excluded 1 review article, 1 duplicate article, 4 articles having ineligible subject, 3 articles having ineligible intervention, and 2 articles having ineligible outcomes data. In the end, we included five research that met the criteria. Conclusion: Low dose aspirin may reduce the incidence of superimposed preeclampsia in pregnant women with cHTN. However, a further investigations is still needed to determine the effectiveness.